2015
DOI: 10.1038/srep18317
|View full text |Cite
|
Sign up to set email alerts
|

Spatially modulated structural colour in bird feathers

Abstract: Eurasian Jay (Garrulus glandarius) feathers display periodic variations in the reflected colour from white through light blue, dark blue and black. We find the structures responsible for the colour are continuous in their size and spatially controlled by the degree of spinodal phase separation in the corresponding region of the feather barb. Blue structures have a well-defined broadband ultra-violet (UV) to blue wavelength distribution; the corresponding nanostructure has characteristic spinodal morphology wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…High-resolution studies of butterfly single scales revealed the 3D photonic nanostructure as a single network of gyroid morphology formed by chitin and air which is reminiscent of cubic phases observed in amphiphilic soft matter systems such as surfactants, block copolymers and lipids in water or block selective solvents. Results supported the hypothesis that color-producing protein and air nanostructures in feather barbs are self-assembled by arrested phase separation of polymerizing β-keratin [56], and the nanostructure can be varied continuously by regulating the time the keratin network is allowed to phase separate before mobility in the system is arrested [131]. In arthropod scales and setae, a richer nanostructural diversity, including triply periodic bicontinuous networks, close-packed spheres, inverse columnar, perforated lamellar, and disordered spongelike morphologies have been reported [130].…”
Section: High Resolution Diffraction and Imagingsupporting
confidence: 66%
See 1 more Smart Citation
“…High-resolution studies of butterfly single scales revealed the 3D photonic nanostructure as a single network of gyroid morphology formed by chitin and air which is reminiscent of cubic phases observed in amphiphilic soft matter systems such as surfactants, block copolymers and lipids in water or block selective solvents. Results supported the hypothesis that color-producing protein and air nanostructures in feather barbs are self-assembled by arrested phase separation of polymerizing β-keratin [56], and the nanostructure can be varied continuously by regulating the time the keratin network is allowed to phase separate before mobility in the system is arrested [131]. In arthropod scales and setae, a richer nanostructural diversity, including triply periodic bicontinuous networks, close-packed spheres, inverse columnar, perforated lamellar, and disordered spongelike morphologies have been reported [130].…”
Section: High Resolution Diffraction and Imagingsupporting
confidence: 66%
“…An important motivation for studying long-range ordered colloidal systems has been from the point of view of potential photonic materials [8]. More recent investigations employed high-resolution SAXS for elucidating the structural basis of colors in biophotonic specimens [57,130,131]. High-resolution studies of butterfly single scales revealed the 3D photonic nanostructure as a single network of gyroid morphology formed by chitin and air which is reminiscent of cubic phases observed in amphiphilic soft matter systems such as surfactants, block copolymers and lipids in water or block selective solvents.…”
Section: High Resolution Diffraction and Imagingmentioning
confidence: 99%
“…Production of non-iridescent blue colour by birds also involves co-localized melanosomes ( figure 2III). These melanin-filled organelles are typically found basal to the spongy layer and serve the critical function of absorbing incoherently scattered white light [36,39,49]. Only a certain percentage of light is scattered by the spongy layer to produce blue, and the remainder is scattered incoherently.…”
Section: (B) Interactions Between Ordered Nanostructures and Pigmentsmentioning
confidence: 99%
“…However, ordered nanostructures lead to structural color that depends strongly on the viewing angle, which limits its practical applications. By contrast, materials with short‐range order, such as colloidal glasses or blue bird feathers, show structural color that is independent of angle. While these materials could in principle be used in applications that require structural color that is indistinguishable from pigment, they also tend to diffuse or multiply scatter light, leading to colors that are not saturated.…”
mentioning
confidence: 99%